The value of development researchers: structural racism, universities and UK Overseas Development Assistance (ODA). Issue 2 (1st April 2022) - Patel, Kamna; Shehabi, Ala'a
Abstract : In this Viewpoint we explore and speculate on the value of development researchers at what is an extraordinary moment in the relationship between UK universities and public research funding from UK Overseas Development Assistance (ODA) in the period following massive cuts to the state aid budget in March 2021. We anchor our exploration in structural racism and its manifestation in the politics of aid and development research conducted in universities, and in the lives of racialised minoritised development researchers. We conclude the Viewpoint with some reflections to help guard against the performative value of Southern researchers in development research.